Сutaneous Vasculitis: Classification, Diagnosis and Differential Diagnosis (Part 2) - Vladislav R. Khairutdinov; Irena E. Belousova; Aleksey V. Samtsov (Vestnik Dermatologii i Venerologii, 2020)
This article is a continuation of the literature review on skin vasculitis. In the first part, information was presented on the current nomenclature and prevalence of vasculitis, pathomorphological changes in the skin, as well as diagnostic algorithms for examining patients with this pathology are reflected.